Spatial and temporal risk factors for the early detection of Trypanosoma brucei rhodesiense sleeping sickness patients in Tororo and Busia districts, Uganda - Odiit, M.; Coleman, P.G.; McDermott, John J.; Fèvre, Eric M.; Welburn, S.C.; Woolhouse, Mark E.J. (Oxford University Press, 2004)
We have carried out a study of risk factors for early detection of Trypanosoma brucei rhodesiense sleeping sickness. Records of sleeping sickness patients from 1987 to 2001 from Tororo and Busia districts in Uganda were reviewed for their village of origin and clinical stage (early or late). All villages that reported sleeping sickness and fixed post-diagnostic sleeping sickness health units in Tororo and Busia districts were geo-referenced. The spatial distribution of early and late stage patient detection by health units was analysed using Geographical Information Systems (GIS). Of 1316 sleeping sickness patients admitted at the Livestock Health Research Institute and Busolwe hospitals and Lumino health centre from Tororo and Busia districts, 471 (35.8%) were early stage, 825 (62.7%) were late stage, while 20 (1.5%) were not staged. Five hundred and eighty-five (44.5%) came from within a 10km radius of the reporting health units. After multivariate analysis, the proportion of early stage patients detected was found to be significantly associated with patients originating from within a 10km radius of the health unit (P19 years) (PP<0.01). Application of GIS and the early to late stages ratio are an informative and powerful means of determining efficiency of surveillance of sleeping sickness.